Identifying and Explaining the Facilitating and Inhibiting Factors of Research Self-Efficacy - Ali Ebrahimi Ghale Ghazi; Kolsum Nami; Mokhtar Zakeri; Mahmoud Sabahizadeh (Iranian Journal of Educational Research)
Objective: Research self-efficacy can be defined as individuals' beliefs and judgments about their own abilities in the field of research. The present study aimed to identify and explain the facilitating and inhibiting factors of research self-efficacy among graduate students at Islamic Azad University in Hormozgan. Methods: The research was conducted using a qualitative approach with an inductive coding system. To identify the factors influencing the research self-efficacy of graduate students, semi-structured interviews were conducted with experts, professors, and research deputies of universities in Hormozgan province. Purposeful sampling was used, and data saturation was reached after 20 interviews. Results: The results showed that 24 factors, such as mastery of research fundamentals, the scientific structure of the university, and student participation in research activities, strengthen research self-efficacy. Conversely, 17 factors, including poor communication between professors, students, and industry, and neglecting students' abilities, had an inhibiting role. Conclusions: Furthermore, effective performance of professors, elimination of traditional teaching methods, strengthening research interactions, and establishing professional connections with researchers were recognized as the most important strategies for enhancing research self-efficacy.